Optimization of 2-dimensional gel electrophoresis for proteomic studies of oil palm roots - Nik Zuriadi, Nik Nur A'in (2015)
2D electrophoresis (2-DE) is a proteomic tool that has been widely used as this technique is capable of resolving and separating thousands of proteins in a single gel for parallel analysis. 2-DE allows the identification of individual protein and understanding of the host-pathogen interaction during their molecular crosstalks. In addition, this modification technique also allows the study of protein profiling of solid biological samples. However, the analytical conditions need to be optimized to achieve optimal parameters and procedures for 2-D gel images. In the present study, optimization was carried out which aimed to improve image quality, reproducibility and sensitivity of 2-D gel. Generally, focusing time and voltage of Isoelectric focusing (IEF) affect the reproducibility of 2-D gel images for protein analysis. It was found that increasing voltage and time for IEF running were optimal for 2-DE. Reducing development time, enhancing the washing step, prolong fixation to overnight and the use of freshly prepared reagents of silver staining produced better image resolution and enhanced sensitivity.